2020
DOI: 10.5194/acp-2020-621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An assessment of the impact of a nation-wide lockdown on air pollution – a remote sensing perspective over India

Abstract: Abstract. The nation-wide lockdown imposed over India from 25th March 2020 onwards, in response to the COVID-19 pandemic, placed severe restrictions upon the industrial and transport sectors, which together form a significant chunk of anthropogenic emissions of pollutants into the atmosphere. Atmospheric concentrations of Nitrogen dioxide (NO2), carbon monoxide (CO) and aerosol optical depth (AOD) for lockdown and pre-lockdown periods were investigated with observations from Aura/OMI, Terra/MOPITT, Sentinel-5p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 10 publications
(12 reference statements)
7
30
0
Order By: Relevance
“…This is potentially linked to the influence of the local emissions which could not be detected by the space-based instruments because of relatively large satellite footprints. The results of percentage change observed by OMI are consistent with the change reported by Pathakoti et al (2020), although Siddiqui et al (2020) reported a higher decline of NO2 using TROPOMI. This is because we computed the changes between lockdown and BAU during the same period of the year whereas Siddiqui et al (2020) estimated the changes between the pre-lockdown NO2 and the lockdown NO2 which includes https://doi.org/10.5194/acp-2020-1023 Preprint.…”
Section: Inter-comparison Of Changes Observed By Omi Tropomi and Sursupporting
confidence: 86%
See 2 more Smart Citations
“…This is potentially linked to the influence of the local emissions which could not be detected by the space-based instruments because of relatively large satellite footprints. The results of percentage change observed by OMI are consistent with the change reported by Pathakoti et al (2020), although Siddiqui et al (2020) reported a higher decline of NO2 using TROPOMI. This is because we computed the changes between lockdown and BAU during the same period of the year whereas Siddiqui et al (2020) estimated the changes between the pre-lockdown NO2 and the lockdown NO2 which includes https://doi.org/10.5194/acp-2020-1023 Preprint.…”
Section: Inter-comparison Of Changes Observed By Omi Tropomi and Sursupporting
confidence: 86%
“…Biswal et al (2020) reported that average OMI NO2 over India decreased by 12.7 %, 13.7 %, 15.9 %, and 6.1 % during the subsequent weeks of the lockdown. Similarly, Pathakoti et al (2020) reported a decrease of 17 % in average OMI NO2 over India as compared to the pre-lockdown period and a decrease of 18 % against the previous 5-year average. Moreover, both the study reported a larger reduction of over 50 % over Delhi.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…3 b. Similarly, a common declining trend of AOD has been recorded in China ( Fan et al, 2020 ; Filonchyk et al, 2020 ), India ( Gautam, 2020 ; Pathakoti et al, 2020 ; Ranjan et al, 2020b ), and South Asia ( Zhang et al, 2020 ).
Fig.
…”
Section: Resultsmentioning
confidence: 80%
“…lockdown, there was a 18% decrease in NO2 over the whole country, with a 54% decrease over New Delhi compared to the same period in 2015-2019 (Pathakoti et al, 2020). In situ measurements in New Delhi showed a 53% decrease in NO2 and a 0.8% increase in O3 for the lockdown period compared to the 2 weeks immediately preceding it.…”
mentioning
confidence: 85%